Design of marine facilities for the berthing, mooring, and repair of vessels - Gaythwaite, John (ASCE Press, 2004)
Suitable for practicing engineers, this handbook covers the design of marine structures for the berthing, mooring, and repair of vessels, including piers, wharves, bulkheads, quaywalls, dolphins, dry docks, floating docks, and various ancillary structures